a) \(x+\dfrac{-7}{15}=-1\dfrac{1}{20}\)
\(\Rightarrow x+\dfrac{-7}{15}=-\dfrac{21}{20}\)
\(\Rightarrow x=-\dfrac{21}{20}-\dfrac{-7}{15}\)
\(\Rightarrow x=-\dfrac{7}{12}\)
b) \(\left(3\dfrac{1}{2}-x\right)\cdot1\dfrac{1}{4}=-1\dfrac{1}{20}\)
\(\Rightarrow\left(\dfrac{7}{2}-x\right)\cdot\dfrac{5}{4}=-\dfrac{21}{20}\)
\(\Rightarrow\dfrac{7}{2}-x=-\dfrac{21}{20}:\dfrac{5}{4}\)
\(\Rightarrow\dfrac{7}{2}-x=-\dfrac{21}{25}\)
\(\Rightarrow x=\dfrac{7}{2}+\dfrac{21}{25}\)
\(\Rightarrow x=\dfrac{217}{50}\)
c) \(\dfrac{1}{2}\cdot x+\dfrac{3}{5}\left(x-2\right)=3\)
\(\Rightarrow\dfrac{1}{2}\cdot x+\dfrac{3}{5}\cdot x-\dfrac{6}{5}=3\)
\(\Rightarrow x\cdot\left(\dfrac{1}{2}+\dfrac{3}{5}\right)=3+\dfrac{6}{5}\)
\(\Rightarrow\dfrac{11}{10}\cdot x=\dfrac{21}{5}\)
\(\Rightarrow x=\dfrac{21}{5}:\dfrac{11}{10}\)
\(\Rightarrow x=\dfrac{42}{11}\)
d) \(\dfrac{11}{12}\cdot x+\dfrac{3}{4}=\dfrac{-1}{6}\)
\(\Rightarrow\dfrac{11}{12}\cdot x=\dfrac{-1}{6}-\dfrac{3}{4}\)
\(\Rightarrow\dfrac{11}{12}\cdot x=-\dfrac{11}{12}\)
\(\Rightarrow x=-\dfrac{11}{12}:\dfrac{11}{12}\)
\(\Rightarrow x=-1\)
\(a,x+\dfrac{-7}{15}=-1\dfrac{1}{20}\)
\(x+\dfrac{-7}{15}=\dfrac{-19}{20}\)
\(x=\dfrac{-19}{20}-\dfrac{-7}{15}\)
\(x=\dfrac{-19}{20}+\dfrac{7}{15}\)
\(x=\dfrac{-285}{300}+\dfrac{140}{300}\)
\(x=\dfrac{-145}{300}\)
\(x=\dfrac{-29}{60}\)
\(b,\left(3\dfrac{1}{2}-x\right).1\dfrac{1}{4}=-1\dfrac{1}{20}\)
\(\left(\dfrac{7}{2}-x\right).\dfrac{5}{4}=\dfrac{-19}{20}\)
\(\dfrac{7}{2}-x=\dfrac{-19}{20}:\dfrac{5}{4}\)
\(\dfrac{7}{2}-x=\dfrac{-19}{20}.\dfrac{4}{5}\)
\(\dfrac{7}{2}-x=\dfrac{-19}{25}\)
\(x=\dfrac{7}{2}-\dfrac{-19}{25}\)
\(x=\dfrac{175}{50}-\dfrac{-38}{50}\)
\(x=\dfrac{137}{50}\)
c,\(\dfrac{1}{2}.x+\dfrac{3}{5}.9\left(x-2\right)=3\)
ko biết làm
\(d,\dfrac{11}{12}.x+\dfrac{3}{4}=\dfrac{-1}{6}\)
\(\dfrac{11}{12}.x=\dfrac{-1}{6}-\dfrac{3}{4}\)
\(\dfrac{11}{12}.x=\dfrac{-4}{24}+\dfrac{-18}{24}\)
\(\dfrac{11}{12}.x=\dfrac{-11}{12}\)
\(x=\dfrac{-11}{12}:\dfrac{11}{12}\)
\(x=\dfrac{-11}{12}.\dfrac{12}{11}\)
\(x=-1\)